Utilization of Mesoporous Silica from Rice Husk to Reduce Copper Level in Water Using Adsorption Method - Saur Lumban Raja; Elisabet Maret Sipayung; Hamonangan Nainggolan (Talenta Publisher, 2024)
Conducted research on the utilization of mesoporous silica derived from rice husks for copper reduction using adsorption methods. This work aims to evaluate the efficacy of copper adsorption with mesoporous silica derived from rice husk, calcined at a temperature of 900 °C. Mesoporous silica possesses a pore diameter ranging from 5 to 17 nm. The approach employed to decrease copper is the adsorption method. Identifying the optimal settings entails an adsorbent mass of approximately 0.2 g, 0.4 g, 0.6 g, 0.8 g, and 1.0 g an adsorbate concentration of 10 mg/l, and a contact duration of 60 minutes. The adsorption technique involves contacting mesoporous silica with a copper solution in an Erlenmeyer flask, followed by stirring with a magnetic stirrer utilizing varying masses of mesoporous silica. The results indicated that a substantial adsorption occurs with the utilization of 1.6 g of mesoporous silica, achieving a copper adsorption percentage of 99.73%. The quantity of adsorbed copper ions is determined by the difference in metal concentration before and after adsorption, evaluated using Atomic Absorption Spectroscopy (AAS).